MAGEB2 antibody as potential diagnostic and predictive tool in the progression of oral cancer / Noratikah Awang Hasyim - Noratikah, Awang Hasyim (2020)
Introduction: Oral squamous cell carcinoma (OSCC) represents more than 90% of all oral cancer. Despite advances in diagnostic and therapeutic modalities, mortality and morbidity rates have not improved in the last decade. Hence, alternative diagnostic and therapeutic approaches are urgently needed. Cancer testes antigens (CTA) are proteins that are expressed in various malignant tumours but its expression in normal tissue is restricted to testes and occasionally placental trophoblast. Due to its exclusive presence in different types of malignant tumors, and their ability to trigger immune responses, CTA are considered promising biomarkers for cancer vaccines. A previous protein array study reported that MAGEB2, a subset of CTA was significantly associated with better prognosis in OSCC patients. Objectives: The objective of this study were to compare the expressions of MAGEB2 antibody in the tissues of normal oral mucosa (NOM), oral potentially malignant disorder (OPMD), and OSCC patient as well as to evaluate the association of MAGEB2 antibody with socio-demographics and clinico-pathological characteristics in OSCC patients, and lastly to determine the association of MAGEB2 expressions with overall survival in OSCC patients. Methods: Immunohistochemical (IHC) staining with MAGEB2 antibody was performed on 10 NOM, 20 OPMD, and 57 OSCC tissues. Kruskal-Wallis test was used to compare MAGEB2 expression between NOM, OPMD, and OSCC tissue. Diagnostic accuracy of MAGEB2 in distinguishing NOM, OPMD, and OSCC tissue and prognostic accuracy of MAGEB2 with sociodemographic and clinico-pathologic characteristics were determined using receiver operating characteristic (ROC) curve. Kaplan-Meier survival analysis was used to determine the association between MAGEB2 expressions with overall survival (OS). iv Results: MAGEB2 expression was seen in 81% of OSCC tissue. The least MAGEB2 expression was observed in OPMD tissue. MAGEB2 expression was significantly higher in OSCC compared to OPMD tissue (p = 0.014). However, there is no significant difference between MAGEB2 expression in NOM Vs OSCC and NOM Vs OPMD tissue. MAGEB2 was able to distinguish OSCC from OPMD tissue with diagnostic accuracy of 61% sensitivity and 80% specificity. There is no significant correlation between MAGEB2 protein expression with socio-demographic, clinico-pathologic characteristics, and OS in OSCC patients. However, a trend of better overall survival in tissues with high MAGEB2 expression was observed in this study. Conclusions: MAGEB2 is a potential diagnostic biomarker in distinguishing OPMD from OSCC tissues. However, there is no significant association between MAGEB2 expression with socio-demographic, clinico-pathological, and OS in OSCC patients. A larger and equal number of sample size along with inclusion of various OPMD cases are recommended for future study